Potential of biologically active plant oils for controlling of Culex pipiens (Diptera: Culicidae) - Khater, Hanem Fathy; Shalaby, Afaf Abdel-Salam (Acta Scientiae Veterinariae, 2018)
The insecticidal effect of six commercially available plant oils was tested against 4 th larval instars of Culex pipiens. Larvae were originally collected from Meit El-Attar, Qalyubia Governorate, Egypt, and then reared in the laboratory until F1 generation. The LC50 values were 32.42, 47.17, 71.37, 83.36, 86.06, and 152.94 ppm for fenugreek (Trigonella foenumgrecum), earth almond (Cyperus esculentus), mustard (Brassica compestris), olibanum (Boswellia serrata), rocket (Eruca sativa), and parsley (Carum ptroselinum), respectively. The tested oils altered some biological aspects of C. pipiens, for instance, developmental periods, pupation rates, and adult emergences. The lowest concentrations of olibanum and fenugreek oils caused remarkable prolongation of larval and pupal durations. Data also showed that the increase of concentrations was directly proportional to reduction in pupation rates and adult emergences. Remarkable decrease in pupation rate was achieved by mustard oil at 1000 ppm. Adult emergence was suppressed by earth almond and fenugreek oils at 25 ppm. In addition, the tested plant oils exhibited various morphological abnormalities on larvae, pupae, and adult stages. Consequently, fenugreek was the most potent oil and the major cause of malformation of both larval and pupal stages. Potency of the applied plant oils provided an excellent potential for controlling C. pipiens.